Learning C# programming with Unity 3D - Okita, Alex (CRC Press, Taylor & Francis Group, 2020)
"For the novice game programmer with no experience with any programming languages. Covers how C# is used to make a game in Unity3D. Interactive examples give C# code meaning. As more complex aspects of C# are explained the interactivity of example games gains depth. Common programming tasks are taught by way of making a game. Thereader will understand how to read and apply C# in Unity3D and apply that knowledge to other development environments that use C#. New to this edition: includes latest C# functionality and feratures; new tips and tricks oo tuples, pattern matching, out variables, local functions, binary laterals, digit separators, null propagator reduces, etc. Key Features Provides a starting point for the first time programmer Examples enable the reader to eventually write a game using Unity 3D Learn to read and understand documentation and the Unity 3D API"--
Keywords: počítačové hry; programování; C# (programovací jazyk); trojrozměrné zobrazování; computer games; programming; C# (programming language); three-dimensional imaging; příručky; handbooks and manuals